BUDAYA SHOPPING DAN KEKRISTENAN - Aksi Bali (Jurnal Ledalero, 2019)
Abstract: This article explores the phenomena that occur in thelife of society, especially urban communities, namely shoppingbehavior, which has become a culture in the modern world.Shopping culture is not only about behavioral phenomena,but the very important is the philosophy behind this culture.Therefore, the shopping culture should be reviewed by Christianethics. Through this article, shopping culture will be specificallyreviewed in the perspective of the Triune God as the ethicalfoundation of the Christian life.Keywords: culture, shopping, Trinity, ethics.